PENGEMBANGAN MODEL PERSEDIAAN ECONOMIC MANUFACTURING QUANTITY (EMQ) DENGAN PRODUK GANDA DAN STOCHASTIC - Sigit Susanto (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
In the current era of globalization, there is freedom of the flow of products that make the competition between companies become more stringent. In order to survive, PT. XYZ must perform its activities effectively and efficiently on all its parts. One of these lines is the warehouse or inventory line. The existing inventory system and run by PT XYZ is a production environment that produces more than one final product and the demand for its products is uncertain. Based on the condition of PT XYZ, the writer approached the existing inventory system at PT XYZ with inventory model of Economic Manufacturing Quantity, multi item, and probabilistic.